Team Approach: Spinopelvic Dissociation. Issue 8 (August 2021) - Wanner, John Paul; Tatman, Lauren; Stephens, Byron; Mitchell, Phillip
Abstract : Spinopelvic dissociation is a complex and variable injury pattern that requires an integrated, multidisciplinary team including orthopaedic trauma and spine surgeons. Protocols and efficient channels of communication should be in place at tertiary Level-I trauma centers to ensure appropriate and timely treatment of patients with spinopelvic dissociation. Patients with spinopelvic dissociation may present with acute neurological deficits and impending cauda equina syndrome, necessitating urgent, coordinated care. Lumbopelvic fixation with sacroiliac screws yields a stable, multiplanar construct that connects the spine to the pelvis and allows for early mobilization.